THE EFFECT OF SPORTS MASSAGE THERAPY ON FITNESS RECOVERY OF FEMALE SOCCER ATHLETES: ANALYSIS OF CREATINE KINASE LEVELS AND PHYSICAL PERFORMANCE - Mahendra, W. D. (Rehabilitation and Recreation, 2025)
Purpose of the work. This study aims to evaluate the effectiveness of sports massage in promoting muscle recovery among female soccer players. The focus is on analyzing changes in creatine kinase (CK) levels, a biomarker of muscle damage, and vertical jump performance, an indicator of muscle power recovery. Methods and materials. Thirty female soccer players were recruited and randomly assigned to two groups. The first group received sports massage as part of their recovery protocol, while the second group performed active stretching exercises following their matches. CK levels were measured at four specific intervals: baseline, immediately after the match, and 24 and 48 hours post-match. Vertical jump performance was also tested at these same intervals to assess recovery progress. A mixed-design ANOVA was employed to investigate changes in CK levels over time and between groups, focusing on significant interactions between these variables. Results. CK levels significantly increased in both groups immediately after the match, reflecting exercise- induced muscle damage. However, the sports massage group demonstrated a faster reduction in CK levels at 24 and 48 hours post-match compared to the active stretching group. This suggests that sports massage facilitates the quicker elimination of muscle damage markers. Additionally, paired t-tests indicated significant improvements in vertical jump performance in the sports massage group by 48 hours postmatch, signifying enhanced muscle power recovery and reduced delayed onset muscle soreness (DOMS). In contrast, the active stretching group exhibited slower recovery, with less pronounced improvements in jump performance. Conclusions. The findings highlight the significant benefits of sports massage as an effective recovery strategy for athletes. By enhancing blood flow, relieving muscle tension, and accelerating the removal of metabolic waste products, sports massage promotes faster recovery and reduces muscle soreness. This allows athletes to restore their performance more efficiently. The study underscores the importance of incorporating sports massage into post-match recovery protocols. Further research is encouraged to explore the underlying physiological mechanisms and optimize recovery strategies for competitive athletes across various sports.